2018
DOI: 10.3390/molecules23092276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Storage Conditions on Phenolic Profiles and Antioxidant Activity of Litchi Pericarp

Abstract: Changes of phenolic profiles and antioxidant activity of litchi pericarp during storage at 4 °C for seven days and at room temperature (RT) for 72 h were evaluated in this study. The contents of total phenolic and procyanidin decreased by 20.2% and 24.2% at 4 °C and by 37.8% and 47.8% at RT, respectively. Interestingly, the corresponding reductions of anthocyanins were 41.3% and 73%, respectively. Four phenolic compounds, including epicatechin, procyanidin A2, procyanidin B2, and quercetin-3-O-rutinoside-7-O-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 37 publications
5
18
0
5
Order By: Relevance
“…After 180 days of storage, the phenol content decreased by 49.87% (FO + B), 23.12% (FO + F), 48.42% (FO + O), 67.45% (FO + R), and 7.64% (FO + C) compared to the beginning, because phenol degradation occurred due to oxidation reactions ( Figure 2 ). These results coincided with the available literature data, which indicate that phenol degradation occurred during storage at room temperature, and that the degree of degradation depended on the concentration, chemical characterization of individual phenolic components, storage conditions, higher enzyme activity, and presence of reactive oxygen species (ROS), particularly hydroxyl radical [ 61 , 62 ].…”
Section: Resultssupporting
confidence: 89%
“…After 180 days of storage, the phenol content decreased by 49.87% (FO + B), 23.12% (FO + F), 48.42% (FO + O), 67.45% (FO + R), and 7.64% (FO + C) compared to the beginning, because phenol degradation occurred due to oxidation reactions ( Figure 2 ). These results coincided with the available literature data, which indicate that phenol degradation occurred during storage at room temperature, and that the degree of degradation depended on the concentration, chemical characterization of individual phenolic components, storage conditions, higher enzyme activity, and presence of reactive oxygen species (ROS), particularly hydroxyl radical [ 61 , 62 ].…”
Section: Resultssupporting
confidence: 89%
“…The retention of total phenolics was more on the refrigeration storage condition compared to room temperature. The higher water loss and enzyme activity at room temperature might be related to oxidation and hydrolysis of phenolics (Ali et al, 2018;Deng et al, 2018). The findings of the present investigation are in line with those reported by Sakhale et al (2015).…”
Section: Total Phenolicssupporting
confidence: 92%
“…Total phenol content was measured using Folin-Ciocalteu method according to Deng et al [17] Approximately 0.5 g freeze-dried pepper powder was extracted using 80% methanol. After 30 min, 0.4 mL of extract was mixed with 2 mL of Folin-Ciocalteu reagent, then 3 mL of Na 2 CO 3 (10%) was added to the mixture and incubated at room temperature for 60 min.…”
Section: Total Phenol Content Measurementmentioning
confidence: 99%
“…The decrease of total phenol content was related to PPO activity. Deng et al [17] found that faster water loss and higher PPO activity in litchi pericarp could accelerate the oxidation of phenolics during storage. The maximum decrease of total phenol was shown in the early 8 days but slowed in the late storage.…”
Section: Total Phenol Contentmentioning
confidence: 99%